IMPLEMENTATION OF E-CRM TO INCREASE CONSUMER INTEREST IN UD.NAZWAN TINGGI RAJA DISTRICT WEB BASED - Sihotang, Rehani Aulia; Manurung, Nuriadi; Latiffani, Chitra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: The development of information technology has experienced very rapid growth, especially the internet. The internet makes a very helpful contribution in the business sector. Tight business competition and the rapid growth of information technology make it easy for customers to switch to other stores. UD. Nazwan has not implemented a service that makes it easier for customers to buy goods easily and is still using the service manually, sales report data is still used in ledgers so it is not efficient to keep neat records, customers have to come directly to the shop to find out what products are being sold so customers are not aware of the latest discounts and products sold in the store. UD. Nazwan is a business that sells pants, shoes, school uniforms, shirts, dresses and sandals. One effort to improve service is by implementing the concept of Customer Relationship Management (CRM). The goal achieved at this stage is the operability of the system design results that have been created. With CRM design, you can increase sales to meet customer needs. This system was created to make it easier for UD. Nazwan sells products, processes data computerizedly and can improve service to customers. Keywords: consumer; E-CRM; UD.nazwan. Abstrak: Perkembangan teknologi informasi telah mengalami pertumbuhan yang sangat pesat terutama internet. Internet memberikan kontribusi yang sangat membantu dalam bidang bisnis. Persaingan bisnis yang ketat dan pesatnya pertumbuhan teknologi informasi memudahkan pelanggan untuk beralih ke toko lain. UD. Nazwan belum menerapkan layanan yang memudahkan pelanggan untuk membeli barang dengan mudah dan masih menggunakan layanan secara manual, data laporan penjualan masih digunakan dalam buku besar sehingga tidak efisien untuk melakukan pencatatan yang tertata rapi, pelanggan harus datang langsung ke toko untuk mengetahui produk apa yang dijual maka pelanggan tidak mengetahui diskon terbaru dan produk yang dijual di toko. UD. Nazwan adalah usaha bisnis yang menjual produk celana, sepatu, seragam sekolah, kemeja, baju dan sendal. Salah satu upaya dalam meningkatkan pelayanan adalah dengan menerapkan konsep Customer Relationship Management (CRM). Tujuan yang dicapai pada tahap ini adalah operabilitas hasil desain sistem yang telah dibuat. Dengan desain CRM, dapat meningkatkan penjualan dalam memenuhi kebutuhan pelanggan. Sistem ini dibuat untuk memudahkan UD. Nazwan dalam menjual produk, mengolah data secara komputerisasi dan dapat meningkatkan pelayanan kepada pelanggan. Kata kunci: E-CRM; konsumen; UD.nazwan